THE DEVELOPMENT OF TARJÎḤ METHOD IN ISLAMIC LAW: TRACING THE THOUGHTS OF MUḤAMMAD ‘ALÎ AL-SÂBÛNÎ IN RAWAÎ’ AL-BAYÂN - Much. Mualim; Didin Baharuddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This article aims to trace the thoughts of Muhammad ‘Ali al-Sâbûni in attempt to develop the tarjîh method through the interpretation of ahkâm verses in Rawâî’ al-Bayân book. This is substantial to study since tarjîh is one of solutions taken by many ulama when there is a contradicting argument. Besides, the tarjîh principles used by al-Sâbûni have distinction compared to other ulama. This is library research included in qualitative study, implementing textual approach and Holsti’s version of content analysis. The analysis tools used in this article are tarjîh theories in usûl al-fiqh, both general theories of al-Shaukânî and al-Âmidi, which were then developed by Wahbah al-Zuhaili, as well as the application theories of tarjîh Ḥusain al- Ḥarbî. The results show that al-Sâbûni in Rawâî’ al-Bayân develops certain tarjîh principles and implements the method which is in accordance with those principles. In this case, there are 22 tarjîh principles and 16 implementation methods, taken from the solid source and basis such as Quran, hadith, theories in ‘ulûm al-Qur’ân and usûl al-fiqh, as well as the arguments of previous ulama. Implementation wise, al-Sâbûni is able to do innovative and objective tarjîh which are far from mazhab’s fanaticism.